Communicating seasonal forecasts to farmers in Kaffrine, Senegal for better agricultural management - Ndiaye, Ousmane; Moussa, Abdoulaye S.; Seck, M.; Zougmoré, Robert B.; Hansen, James (2013)
Our project explaining seasonal forecasting to farmers in central Senegal built common ground between scientific forecasting and traditional knowledge. It helped farmers understand and use seasonal forecasts to improve crop strategies, and let farmers explain to meteorologists what seasonal climate information they most needed, in turn improving the forecasts’ usefulness.